2009
DOI: 10.1038/clpt.2009.154
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram Is a Weak Inhibitor of the CYP2D6-Catalyzed O-Demethylation of (+)-Tramadol but Does Not Reduce the Hypoalgesic Effect in Experimental Pain

Abstract: Tramadol is O-demethylated to the active metabolite (+)-O-desmethyltramadol ((+)-M1) via CYP2D6, an enzyme that is weakly inhibited by escitalopram. We investigated the possibility of a pharmacokinetic (PK) and pharmacodynamic (PD) effect of escitalopram on tramadol metabolism. Fifteen healthy subjects completed this randomized, double-blind, three-phase, crossover trial. Combinations of escitalopram 20 mg/day or placebo together with tramadol 150 mg or placebo were used. Blood samples for pharmacokinetics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…However, available clinical data provide controversial results regarding the analgesic effi cacy of tramadol in subjects with different CYP2D6 phenotype/genotype. Some clinical studies revealed decreased analgesic effi cacy in CYP2D6 poor metabolizers (11) in line with experimental model of pain (12), while inhibition of CYP2D6 by escitalopram did not impair the analgesic effect of tramadol in another study although there was a shift in drug pharmacokinetics confi rming decreased CYP2D6 (13). This is in line with different observations in pain model in healthy volunteers, in which PM subjects reported analgesia during electrical stimulation test (14).…”
supporting
confidence: 77%
“…However, available clinical data provide controversial results regarding the analgesic effi cacy of tramadol in subjects with different CYP2D6 phenotype/genotype. Some clinical studies revealed decreased analgesic effi cacy in CYP2D6 poor metabolizers (11) in line with experimental model of pain (12), while inhibition of CYP2D6 by escitalopram did not impair the analgesic effect of tramadol in another study although there was a shift in drug pharmacokinetics confi rming decreased CYP2D6 (13). This is in line with different observations in pain model in healthy volunteers, in which PM subjects reported analgesia during electrical stimulation test (14).…”
supporting
confidence: 77%
“…In vivo studies [12,13,14] have shown that citalopram and escitalopram are weak inhibitors of CYP2D6 [15]. Demethylcitalopram is a more potent inhibitor of CYP2D6 than citalopram and may mediate some mild interaction with other drugs metabolized by CYP2D6 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Escitalopram could significantly decrease the median AUC (0–infinity) of (+)-M1 by 29%, but it did not impair the analgesic effect of tramadol assessed by the cold pressor test 61. The underlying mechanism may be that escitalopram is a weak inhibitor of CYP2D6 whereas paroxetine is a strong CYP2D6 inhibitor.…”
Section: Resultsmentioning
confidence: 91%